Identification of Chitinase-3-Like Protein 1 as a Novel Neutrophil Antigenic Target in Crohn's Disease. (7th February 2019) - Deutschmann, Claudia; Sowa, Mandy; Murugaiyan, Jayaseelan; Roesler, Uwe; Röber, Nadja; Conrad, Karsten; Laass, Martin W; Bogdanos, Dimitrios; Sipeki, Nora; Papp, Maria; Rödiger, Stefan; Roggenbuck, Dirk; et al.
Abstract: Background and Aims: There is an increasing incidence of inflammatory bowel disease [IBD]. Autoimmune responses are involved in the pathophysiology of IBD, but their underlying pathways and target antigens have not yet been fully elucidated. Methods: Autoantigenic targets in IBD were identified after separation of whole cell proteins isolated from neutrophils using two-dimensional electrophoresis and matrix assisted laser desorption ionization – time of flight mass spectrometry-based protein identification of the spots that displayed Western blotting signals with anti-neutrophil cytoplasmic antibody-positive sera. The prevalence of IgG, IgA and secretory IgA [sIgA] to chitinase 3-like protein 1 [CHI3L1] was analysed by enzyme-linked immunosorbent assays using recombinant CHI3L1 in 110 patients with Crohn's disease [CD], 95 with ulcerative colitis [UC], 126 with coeliac disease [CeD] and 86 healthy controls [HCs]. Results: The 18-glycosylhydrolase family member CHI3L1 was identified as a neutrophil autoantigenic target. CD patients displayed significantly higher levels of IgG to CHI3L1 than patients with UC and CeD ( p < 0.0001, respectively). IgA and sIgA to CHI3L1 was significantly higher in CD than in UC, CeD and HCs [ p < 0.0001, respectively]. IgA and sIgA to CHI3L1 demonstrated the highest prevalence in CD [25.5%, 28/110; and 41.8%%, 46/110] compared to HCs [2.3%, 2/86; and 4.7%%, 4/86; p = 0.0015 and p < 0.0001] and are associated with a more complicated progression of CD. Conclusion: CHI3L1 is a novel neutrophil autoantigenic target in CD. IgA and sIgA to CHI3L1 may serve as novel markers for CD and may facilitate the serological diagnosis of IBD.